Weak convergence theorem for Passty type asymptotically nonexpansive mappings - B. K. Sharma; B. S. Thakur; Y. J. Cho (International Journal of Mathematics and Mathematical Sciences)
In this paper, we prove a convergence theorem for Passty type asymptotically nonexpansive mappings in a uniformly convex Banach space with Fréchet-differentiable norm.